Sosialisasi Strategi Mitigasi Petani terhadap Perubahan Iklim di Korong Sijangek Kanagarian Sungai Durian Kecamatan Patamuan Kabupaten Padang Pariaman. - Ade - ASuryani (STKIP PGRI Sumatera Barat, 2019)
Changes in global climate that changes the average global temperature increases. Increased greenhouse gas emissions in the atmosphere, specifically CO2, have trapped heat in the Earth's atmosphere. This has an impact on the global system that causes everything from unexpected rainfall to extreme heat waves. The earth has gone through a period of warming and which is associated with repeated changes. What is currently the main concern and carried out by researchers is the heating process which is carried out faster than previously done, and also the increases associated with increasing levels of human production. The method of service activities that are used, among others: Lecture The use of laptops and LCDs helps socialization participants more easily discuss socialization material, relatively more material and limited training time, Demonstrations. Demonstrations were carried out by the service team as a source in the hope that the training participants could be carried out in accordance with the instructions given by the nara sources. Keywords: Socialization. Mitigation. Climate change.